(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
Roentgen structural and optical (optical polarizing microscope) investiga-tions showed that potassium persulfate and cetylpyridinium bromide have crystal structure. The product of their interaction in contrast to the originals is an amorphous substance.